Incidence and long-term specific mortality trends of metabolic syndrome in the United States - Li, Weiya; Qiu, Xinfan; Ma, Huan; Geng, Qingshan (Frontiers in Endocrinology, 2023)
Purpose: Metabolic syndrome (MetS) is very prevalent and related to severe diseases and death. This study aims to investigate the incidence and mortality trends of MetS in recent decades. The gender and age differences of MetS are also been explored. Patients and methods: Patients with MetS were screened in the National Health and Nutrition Examination Survey (NHANES) adults from 1999 to 2014. The mortality data of them was also acquired. Then we assessed the incidence and mortality trends of MetS in the US. Results: 14171 participants were included in our study, in which the mean age was 46.8±19.3 years and 7354 (51.9 %) were female. 4789 participants finally were diagnosed with MetS. The overall trend of incidence of MetS from 1999 to 2014 was upward (from 27.6 to 32.3%; adjusted odds ratios [aOR], 1.71; 95% confidence interval [CI], 1.42-2.05; P-value <0.001, P for trend <0.001). In more detail, the incidence of MetS rose first but subsequently stalled and declined. Obvious downward trends were observed from 29.6 to 2.7% for all-cause mortality (aOR, 0.12; 95%CI, 0.07-0.21; P-value <0.001, P for trend <0.001) and 4.8 to 0.8% for cardio-cerebrovascular mortality (aOR, 0.17; 95%CI, 0.05-0.61; P-value =0.007, P for trend <0.001). The all-cause mortality had a yearly decline trend, while the cardio-cerebrovascular death experienced a short period of rise then declined and stabilized. Similarly, the temporal mortality trends in MetS patients of different ages and gender had the same results. Specifically, the incidence of MetS in females was higher than that in males (Adjusted P =0.003; OR, 1.14; 95%CI, 1.05-1.24), but the mortality was much lower after a long-term follow-up (All-cause mortality, Adjusted P <0.001; Hazard Ratio [HR], 0.68; 95%CI, 0.57-0.81; Cardio-cerebrovascular mortality, Adjusted P =0.004; HR, 0.55; 95%CI, 0.37-0.83). Conclusion: From 1999-2014, the incidence of MetS in U.S. adults significantly increased overall, while the mortality rate of MetS had a significant downward trend. Both trends showed marked gender differences, being more prevalent and at lower risk in females compared with males. It is important to identify the factors to curb the incidence of MetS and decrease mortality, especially in males.